SLR : Analisis Faktor yang Mempengaruhi Pengambilan Keputusan Karir - Alfito Fatihah; Cyntia Suarni Arifin; Desmi Fitri Syahdani Br Sitepu; Nur Aisyah; Syifa Husna Ramadhani; Mayang Nabila; Zulaily Syahrani; Siti Salamah Br Ginting (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
In everyday life, decision making is an unavoidable activity, both in personal, organizational and societal contexts. Each individual or group is often faced with various alternative choices, where each choice has certain consequences. In your career, decision making is very important. In making a decision there are definitely factors that influence it. In this research, the author used the Systematic Literature Review (SLR) method This research uses a Systematic Literature Review (SLR) approach with data sources originating from previous journal literature. Data collection was carried out by documenting all articles and journals that were relevant to this research. From 20 similar articles, researchers took 10 articles to analyze and summarize. The results of this research show that the factors that influence career decision making are internal factors which include self-efficacy, motivation, interests, skills and personal perceptions, which are the psychological and emotional basis for individuals in determining their career direction, as well as external factors such as family support, the environment. Social, economic opportunities, capital, and market conditions play a significant role in providing resources and external incentives that support career decision making.